Circular RNAs: pivotal role in the leukemogenesis and novel indicators for the diagnosis and prognosis of acute myeloid leukemia - Rahmati, Atefe; Mafi, Alireza; Soleymani, Firooze; Babaei Aghdam, Zahra; Masihipour, Niloufar; Ghezelbash, Behrooz; Asemi, Reza; Aschner, Michael; Vakili, Omid; Homayoonfal, Mina; Asemi, Zatollah; Sharifi, Mehran; et al. (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy and affected patients have poor overall survival (OS) rates. Circular RNAs (circRNAs) are a novel class of non-coding RNAs (ncRNAs) with a unique loop structure. In recent years, with the development of high-throughput RNA sequencing, many circRNAs have been identified exhibiting either up-regulation or down-regulation in AML patients compared with healthy controls. Recent studies have reported that circRNAs regulate leukemia cell proliferation, stemness, and apoptosis, both positively and negatively. Additionally, circRNAs could be promising biomarkers and therapeutic targets in AML. In this study, we present a comprehensive review of the regulatory roles and potentials of a number of dysregulated circRNAs in AML.